The Na+/Ca2+ exchanger NCX3 mediates Ca2+ entry into matrix vesicles to facilitate initial steps of mineralization in osteoblasts - Irshad A. Sheikh; Monica T. Midura‐Kiela; André Herchuelz; Sophie Sokolow; Pawel R. Kiela; Fayez K. Ghishan (Journal of Extracellular Vesicles, 2024)
Abstract Matrix vesicles (MVs) provide the initial site for amorphous hydroxyapatite (HA) formation within mineralizing osteoblasts. Although Na+/Ca2+ exchanger isoform‐3 (NCX3, SLC8A3) was presumed to function as major Ca2+ transporter responsible for Ca2+ extrusion out of osteoblast into the calcifying bone matrix, its presence and functional role in MVs have not been investigated. In this study, we investigated the involvement of NCX3 in MV‐mediated mineralization process and its impact on bone formation. Using differentiated MC3T3‐E1 cells, we demonstrated that NCX3 knockout in these cells resulted in a significant reduction of Ca2+ deposition due to reduced Ca2+ entry within the MVs, leading to impaired mineralization. Consequently, the capacity of MVs to promote extracellular HA formation was diminished. Moreover, primary osteoblast isolated from NCX3 deficient mice (NCX3−/−) exhibits reduced mineralization efficacy without any effect on osteoclast activity. To validate this in vitro finding, μCT analysis revealed a substantial decrease in trabecular bone mineral density in both genders of NCX3−/− mice, thus supporting the critical role of NCX3 in facilitating Ca2+ uptake into the MVs to initiate osteoblast‐mediated mineralization. NCX3 expression was also found to be the target of downregulation by inflammatory mediators in vitro and in vivo. This newfound understanding of NCX3's functional role in MVs opens new avenues for therapeutic interventions aimed at enhancing bone mineralization and treating mineralization‐related disorders.